Quasi-static loading analysis of fiber metal laminated plates and beams - Sagar Sampath Kumar (2018)
Quasi-Static loading analysis as an analogous to low-velocity impacts on the hybrid Fiber Metal Laminate (FML) is a conscious effort to characterize and study the damage mechanism associated with the one of the most common causes of failure in the hybrid material. With the latest furor in the field of FML structures: a lighter yet stronger alternative to conventional metals, extensive work has been carried out in analyzing quasi-static loading with regards to quantifying damage and predicting the onset of damage because of the barely visible impact damage. However variation in the constituent build-up of the material yields varied responses; the effect of the stacking sequence, the influence and contribution ofthe plasticity offered by the metallic element to the overall response, and the investigation of the damage behavior as a result of using different alloys of the same metal are some important aspects that require discemment. This report details the quasi-static loading analysis of FMLed circular plates and beams. A set of composite plate specimens with varying stacking sequences were fabricated and subjected to controlled quasi-static loading (lmm/min). FML plates and beams were fabricated with pre-calculated varying metal volume fractions (MVF) were also analyzed. Two sets of FML plates with two different aluminum alloys (AI 2024-T3 and 0) were also subjected to the quasi-static loading. Experiments revealed that a quasiisotropic stacking orientation exhibited enhanced load bearing and damage tolerance behavior than other stacking sequences. It was also realized that increasing MVF delayed the onset of damage, but lowers the load bearing capacity, and worsens the damage tolerance and resistance. It is leamed that Al2024-0, displays highly enhanced plasticity, but significantly lower load bearing capacity. It demonstrated better damage resistance than a similar FML plate with Al 2024-T3 alloy. A systematic finite element analysis (FEA) of all the above cases were performed using the commercial software, Abaqus. in order to study the progressive distribution of stress, explicitly analyze the failure associated with each damage mode and also to validate the experimental results. The numerical simulation was found to be in fairly good agreement with the experimental results in terms of force history and damage behavior.